Technical innovations to reduce complication rates in esophageal atresia with particular reference to long-term outcomes: A single surgeon's experience of 22 years - Ahmed Morsi; Devesh Misra (Wolters Kluwer Medknow Publications, 2022)
Background: Following esophageal atresia/tracheoesophageal fistula (EA/TEF) repair, the standard leak rate reported in the literature is 5%-10%, and stricture rate is 40%-72%. There is a global quest for surgical innovations to drive down these complication rates which can cause considerable morbidity. Methods: A prospectively maintained database of the senior author's patients who had esophageal atresia repair from 1995 to 2016 was reviewed. Two distinct innovations were implemented: (1) adequate or generous mobilization of the lower esophageal pouch and (2) a 2-5 mm slit in distal esophagus to widen its circumference. Results: Forty-three patients with EA/TEF were reviewed. Of those, 40 underwent primary repair. The median follow-up was 12.5 years (range 4-26 years). There were no anastomotic leaks and only 8 (20%) patients developed anastomotic strictures requiring dilations (1-5 dilations/patients). One patient (2.5%) had a recurrent fistula. One early mortality was recorded. At the latest follow-up, 35 (87.5%) patients had normal oral feeding, while 1 (2.5%) patient had occasional food sticking episodes. Four syndromic patients (10%) were on jejunal or gastrostomy feeding. Conclusion: An adequate or generous mobilization of the distal esophageal pouch, together with a 2-5 mm slit in the distal esophagus, achieves a tension-free and wide anastomosis. All anastomoses eventually narrow, sometimes just a little, and starting on a higher scale with a small slit, helps. These seemingly minor innovations, when used together, contributed to a substantially lower complication rate sustained over a 22-year period - no leaks and only 20% stricture rate.